One time quantitative PCR detection of Pseudomonas aeruginosa to discriminate intermittent from chronic infection in cystic fibrosis - Boutin, Sébastien; Weitnauer, Michael; Gräber, Simon Y.; Stahl, Mirjam; Dittrich, A. Susanne; Mall, Marcus A.; Dalpke, Alexander (Journal of cystic fibrosis, 2018)
Background - Chronic airway infection with Pseudomonas aeruginosa is a major risk factor of progression of lung disease in patients with cystic fibrosis (CF). Chronic P. aeruginosa infection evolves from intermittent infection that is amenable to antibiotic eradication, whereas chronically adapted P. aeruginosa becomes resistant to antibiotic therapy. Discrimination of intermittent versus chronic infection is therefore of high therapeutic relevance, yet the available diagnostic methods are only partly satisfactory. The aim of the present study was, therefore, to evaluate the usage of quantitative PCR (qPCR) to measure pathogen abundance and to discriminate between intermittent and chronic Pseudomonas infection in patients with CF. - Method - Using an established qPCR protocol, we analyzed the abundance of P. aeruginosa in 141 throats swabs and 238 sputa from CF patients with intermittent or chronic infection with P. aeruginosa, as determined by standard culture based diagnostics. - Results - We observed a large increase of abundance of P. aeruginosa in throat swabs and sputum samples from patients with chronic compared to intermittent infections with P. aeruginosa. The data show that abundance of P. aeruginosa as measured by qPCR is a valuable tool to discriminate intermittent from chronic infection. Of note, P. aeruginosa burden seems more sensitive than mucoidity phenotype to discriminate chronic from intermittent strains. Furthermore we observed that molecular detection in throat swabs was linked to a viable culture in the sputum when sputum was available. This result is of special interest in young patients with cystic fibrosis that often cannot expectorate sputum. We also observed that qPCR in comparison to culture detected the infection earlier. - Conclusion - The results suggest that qPCR detection and quantification of P. aeruginosa is a precious tool to be added to the diagnostic toolbox in cystic fibrosis.
Gesehen am 15.07.2019